Painful rash with hoarseness: an atypical presentation of syphilis - Hanlon, Courtney L (BMJ Case Rep, 2018)
Syphilis is a sexually transmitted disease that can affect multiple organ systems, with central nervous system involvement at any stage. We present a 53-year-old woman with an unusual truncal rash with painful anogenital lesions, accompanied by patchy alopecia, oral lesions, photophobia and hoarseness. She was found to have positive serological tests for syphilis with cerebrospinal fluid findings suggestive of neurosyphilis. She underwent a 14-day course of intravenous penicillin G and exhibited successful resolution of painful anogenital lesions as well as marked improvement in dermatological, oropharyngeal, laryngeal, and neurological symptoms.